A preparation method of a composite solid-state electrolyte based on a Janus particle constructed root-soil interlocking structure
Patent Information
- Application Number
- CN202510412226.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-04-03
AI Technical Summary
但LLZO与锂金属之间的界面可能会在长期使用中发生反应,导致锂的枝晶生长或电解质失效以及LLZO材料具有较大的机械脆性,容易发生断裂或裂纹,尤其在充放电过程中锂电池的膨胀和收缩可能导致电解质的破裂
1)本发明合成了一种多功能分区的Janus改性材料Fe3O4/SiO2@ PVDF,与LLZO形成构筑牢固的根土互锁结构,从而实现LLZO、Janus和PVDF强烈的相互作用。
Smart Images

Figure CN120015907B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion solid electrolyte manufacturing, specifically relating to a method for preparing a composite solid electrolyte based on a root-soil interlocking structure constructed from Janus particles. Background Technology
[0002] Traditional energy sources such as coal, oil, and natural gas have supported global energy demand, but as environmental and resource depletion issues become more prominent, people are turning to clean and sustainable energy sources. Electricity, due to its renewable and environmentally friendly characteristics, has become a key energy conversion and storage medium. Lithium-ion batteries, as a type of energy storage technology, are widely used in portable electronic devices, electric vehicles, and grid energy storage due to their high energy density, long lifespan, and low self-discharge rate.
[0003] The performance of lithium-ion batteries is mainly reflected in their high energy density, which means they can store more electrical energy in a smaller volume and weight (LI M, WANG C, CHEN Z, et al. New Concepts in Electrolytes [J]. Chemical Reviews, 2020, 120(14): 6783-819). Furthermore, they have high charge-discharge efficiency and long cycle life, making them more economical and environmentally friendly in long-term use. However, due to the extremely high chemical reactivity of the lithium metal anode, it reacts with the liquid electrolyte, leading to uneven lithium deposition and safety issues such as combustion or explosion. This limits the commercial application of lithium metal batteries due to many safety concerns (AXK, BYW, CLD, et al. Cell failures of all-solid-state lithium metal batteries with inorganic solid electrolytes: Lithiumdendrites [J]. Energy Storage Materials, 2020, 33: 309-28). Therefore, designing highly safe solid-state lithium metal batteries is crucial for practical applications.
[0004] Inorganic solid electrolytes exhibit fewer side reactions with metal anodes, possessing advantages such as high safety, long lifespan, and leak-proof properties, which can fundamentally address safety hazards. Solid-state lithium batteries assembled with inorganic solid electrolytes are expected to achieve high energy densities (>300 Wh / kg) (LU Z, YANG Z, LI C, et al. Modulating nano-inhomogeneity atelectrode-solid electrolyte interfaces for dendrite-proof solid-state batteries and long-life memristors [J]. 2020). However, inorganic solid electrolytes lack fluidity, and the small contact area at the electrolyte-lithium metal interface formed by solid-solid contact leads to slow ion transport and high impedance. This interface problem has become a bottleneck restricting the development of inorganic solid electrolytes.
[0005] Research has found that: LLZO (solid electrolyte lithium lanthanum zirconium oxide Li7La3Zr2O) 12 LLZO possesses a series of advantages, including high lithium-ion conductivity, stability to lithium metal electrodes, stable electrochemical performance, and the potential for miniaturization. However, the interface between LLZO and lithium metal may react during long-term use, leading to lithium dendrite growth or electrolyte failure. Furthermore, LLZO materials exhibit significant mechanical brittleness, making them prone to fracture or cracking, especially during charge-discharge cycles where the expansion and contraction of the lithium battery can cause electrolyte rupture. This adversely affects battery stability and lifespan. This issue impacts the long-term stability of LLZO and the cycle performance of the battery.
[0006] This invention proposes to construct a root-soil interlocking structure by designing a multifunctional, partitioned organic-inorganic composite Janus material that self-orients between the ceramic and polymer electrolyte. This ensures good and uniform dispersion of the ceramic while improving the interfacial stability of the polymer / ceramic, which is beneficial to Li + The extended amorphous regions provide continuous 3D interconnected paths for realizing long-period Li + Transmission stability is provided as an important guarantee. Summary of the Invention
[0007] The purpose of this invention is to provide a method for preparing a composite solid electrolyte based on a root-soil interlocking structure constructed from Janus particles, addressing the technical problems existing in the background art.
[0008] This invention designs and synthesizes a multifunctional partitioned Janus material Fe3O4 / SiO2@PVDF. Its silica end forms a coordination bond with N-(3-triethoxysilylpropyl)-4,5-dihydroimidazole (DI) on the surface of LLZO material, while its polymer end spontaneously forms a strong root-soil interlocking structure towards the PVDF polymer electrolyte, thereby achieving a strong interaction between LLZO, Janus and PVDF and improving the interfacial stability of the polymer / ceramic.
[0009] The technical solution adopted to achieve the purpose of this invention is as follows: a method for preparing a composite solid electrolyte based on a root-soil interlocking structure constructed from Janus particles, comprising the following preparation steps: 1) Surface modification of SiO2 particles SiO2 particles were dispersed in a mixed solution of ethanol and deionized water and treated with ultrasound to ensure uniform dispersion of the SiO2 particles, thus obtaining a SiO2 particle solution. The SiO2 particle solution was then mixed with the coupling agent 3-aminopropyltriethoxysilane, and centrifuged and washed after the reaction was complete. 2) Preparation of PVDF latex seed solution Using water as the continuous phase, sodium dodecyl sulfate surfactant, potassium persulfate initiator and vinyl fluoride monomer are added to emulsify the vinyl fluoride monomer to form an oil / water emulsion. Polymerization is initiated by heating to form nano-sized PVDF latex particles, thus preparing a PVDF latex seed solution. 3) Preparation of SiO2@PVDF core-shell composite particles The surface-modified SiO2 particles from step 1) were ultrasonically dispersed in the PVDF latex seed solution prepared in step 2). The SiO2 particles were anchored to the surface of the PVDF latex particles by electrostatic adsorption to obtain seed particles. Subsequently, the polymeric monomer vinyl fluoride was added and the reaction temperature was controlled to continue initiating polymerization, allowing the polymeric monomer vinyl fluoride to grow on the surface of the seed particles to form SiO2@PVDF core-shell composite particles. After the reaction was completed, carbon disulfide was added as a terminator to terminate the polymerization reaction. The obtained SiO2@PVDF core-shell composite particles were then washed by centrifugation with deionized water and ethanol. Finally, the SiO2@PVDF core-shell composite particles were obtained after vacuum drying. 4) Preparation of Fe3O4 / SiO2@PVDF The SiO2@PVDF core-shell composite particles obtained in step 3) were ultrasonically dispersed in distilled water, mechanically stirred and argon gas was introduced, then anhydrous ferric chloride and ferrous sulfate heptahydrate were added, and ammonia water was added dropwise to adjust the pH to alkaline. The mixture was stirred to react fully. The product was washed with ethanol and deionized water by centrifugation, and then freeze-dried under vacuum to obtain the final product Fe3O4 / SiO2@PVDF. 5) Modification of LLZO ceramic electrolytic sheets LLZO ceramic electrolytic sheets were pretreated by immersing them in NaOH solution, and then the NaOH solution on the surface of the LLZO ceramic electrolytic sheets was washed away with ethanol to obtain pretreated LLZO ceramic electrolytic sheets. Ethanol, water and N-(3-triethoxysilylpropyl)-4,5-dihydroimidazole were mixed in a certain proportion to prepare a mixed solution. The pretreated LLZO ceramic electrolytic sheets were added to the mixed solution and ultrasonically dispersed, and then subjected to reflux reaction. 6) Preparation of LLZO / Fe3O4 / SiO2@PVDF composite solid electrolyte material N,N-dimethylamide, polyvinylidene fluoride matrix, and Fe3O4 / SiO2@PVDF prepared in step 4) were mixed and stirred evenly, then spread on the surface of LLZO ceramic electrolytic sheet, and baked in a vacuum oven to obtain LLZO / Fe3O4 / SiO2@PVDF composite solid electrolyte material, that is, composite solid electrolyte based on Janus particles constructing root-soil interlocking structure.
[0010] Preferably, in step 1) of the present invention, the particle size of the SiO2 particles is 15 nm, the mass-to-volume ratio of the SiO2 particles to the mixed solution is (1-2) g: 10 mL, the mixed solution is prepared by mixing ethanol and deionized water at a volume ratio of 9:1, and the ultrasonic treatment time is 30-60 min; the mass-to-volume ratio of the SiO2 particle solution to the coupling agent 3-aminopropyltriethoxysilane is 20: (3-5).
[0011] Preferably, in step 2) of the present invention, the mass ratio of the surfactant sodium dodecyl sulfate to the polymeric monomer vinyl fluoride is (0.18-0.3):(10-14); and the mass ratio of the initiator potassium persulfate to the polymeric monomer vinyl fluoride is (0.12-0.28):(10-14).
[0012] Preferably, in step 3) of the present invention, the mass-to-volume ratio of the polymerizable monomer vinyl fluoride to the terminator carbon disulfide is 1 g: (0.01-0.03) mL, and the reaction temperature for initiating polymerization is controlled at 60℃-80℃.
[0013] Preferably, in step 4) of the present invention, the mass-to-volume ratio of the SiO2@PVDF core-shell composite particles to distilled water is 1g:20mL, and the mass ratio of the SiO2@PVDF core-shell composite particles to anhydrous ferric chloride and ferrous sulfate heptahydrate is 10:(3-5):(2-3).
[0014] Preferably, the volume ratio of ethanol, water and N-(3-triethoxysilylpropyl)-4,5-dihydroimidazole in step 5) of the present invention is 9:2.5:1.
[0015] Preferably, in step 5) of the present invention, the pretreated LLZO ceramic electrolytic sheet is added to the mixed solution and ultrasonically dispersed for 30-60 min, then refluxed in an oil bath at 75°C with a spherical condenser tube for rotor stirring, and reacted for 24 h.
[0016] Preferably, the volume-to-mass ratio of N,N-dimethylamide, polyvinylidene fluoride and Fe3O4 / SiO2@PVDF in step 6) of the present invention is (5-8) mL: (1-1.6) g: (0.1-0.5) g.
[0017] Preferably, in step 6) of the present invention, the temperature of the vacuum oven is 80°C and the baking time is 24 hours.
[0018] Compared with the prior art, the technical advantages of the present invention are as follows: 1) This invention synthesizes a multifunctional partitioned Janus modified material Fe3O4 / SiO2@PVDF, which forms a robust root-soil interlocking structure with LLZO, thereby achieving a strong interaction between LLZO, Janus and PVDF.
[0019] 2) The Janus-modified material Fe3O4 / SiO2@PVDF of the present invention optimizes the contact between LLZO material and electrolyte or electrode through two different interfacial properties: hydrophilicity and hydrophobicity. This improves ion migration efficiency and interfacial stability, and overcomes the limitations of traditional LLZO materials in terms of interfacial contact.
[0020] 3) The introduction of PVDF in this invention enables Janus-modified material Fe3O4 / SiO2@PVDF to maintain high electrical conductivity while possessing better mechanical strength and flexibility, thus better adapting to the high-stress environment of lithium batteries. Due to the optimized performance of this material, Fe3O4 / SiO2@PVDF-modified LLZO material also has significant advantages in improving battery performance, especially under extreme conditions such as high temperature and high voltage, it can maintain high conductivity and stability, reducing safety issues caused by material deformation or degradation. Attached Figure Description
[0021] Figure 1 This is a schematic diagram of the bridging between the Janus organic-inorganic composite electrolyte and the electrode surface in this invention.
[0022] Figure 2 This is a microstructure diagram of the LLZO / 0.3Fe3O4 / SiO2@PVDF sample synthesized in Example 3 of the present invention.
[0023] Figure 3 This is a cross-sectional view of the LLZO / 0.3Fe3O4 / SiO2@PVDF sample synthesized in Example 3 of the present invention.
[0024] Figure 4 The AC impedance spectra of the ceramic samples synthesized in Examples 1, 3, and 5 of this invention, as well as the synthesized LLZO / xFe3O4 / SiO2@PVDF (x=0.1, 0.3, 0.5) and the LLZO / SiO2@PVDF ceramic samples synthesized in Comparative Example 2, are shown.
[0025] Figure 5 The samples synthesized and assembled into coin cells LFP / LLZO / xFe3O4 / SiO2@PVDF / Li (x=0.1, 0.3, 0.5) in Examples 1, 3, 5 and Comparative Example 2 of this invention are shown, and their cycle performance at 0.1C is evaluated. Detailed Implementation
[0026] The present invention will be further described below with reference to embodiments and comparative examples. Example 1:
[0027] 1) Surface modification of SiO2 particles: 2g of commercially available SiO2 particles (15nm in diameter) were dispersed in 20mL of a mixed solution of ethanol and deionized water, with a volume ratio of ethanol to deionized water of 9:1. The solution was ultrasonically treated for about 30min to ensure uniform dispersion of the SiO2 particles, thus obtaining a SiO2 particle solution. The SiO2 particle solution was then mixed with 3mL of silane coupling agent 3-aminopropyltriethoxysilane (APTES) and reacted for 2 hours to modify the surface of the SiO2 particles. Finally, excess silane coupling agent was removed by centrifugation and the particles were washed.
[0028] 2) Preparation of PVDF latex seed solution Using water as the continuous phase, 0.18 g of sodium dodecyl sulfate surfactant, 0.12 g of potassium persulfate initiator, and 10 g of vinyl fluoride monomer were added. The vinyl fluoride monomer was emulsified to form an oil / water emulsion, and the temperature was raised to 60℃ to initiate polymerization, forming nano-sized PVDF latex particles, thus obtaining a PVDF latex seed solution.
[0029] 3) Preparation of SiO2@PVDF core-shell composite particles The surface-modified SiO2 particles from step 1) were ultrasonically dispersed in the PVDF latex seed solution prepared in step 2). The SiO2 particles were anchored to the surface of the PVDF latex particles using electrostatic adsorption to obtain seed particles. Subsequently, 5g of the monomer vinyl fluoride was added, and the reaction temperature was controlled at 60℃ to continue polymerization for 4 hours, allowing the vinyl fluoride monomer to grow on the surface of the seed particles, forming SiO2@PVDF core-shell composite particles. After the reaction, 0.05 mL of carbon disulfide was added as a terminator to terminate the polymerization. Unreacted vinyl fluoride monomer and potassium persulfate initiator were removed by centrifugation. The obtained SiO2@PVDF core-shell composite particles were washed multiple times by centrifugation with deionized water and ethanol to remove residual reactants and the surfactant sodium dodecyl sulfate. Finally, the washed SiO2@PVDF core-shell composite particles were dried in a vacuum drying oven at 60℃ for 12 hours to room weight.
[0030] 4) Preparation of Fe3O4 / SiO2@PVDF 10g of SiO2@PVDF core-shell composite particles were ultrasonically dispersed in 200 mL of distilled water in a three-necked flask, mechanically stirred, and argon gas was introduced. Then, 3g of anhydrous ferric chloride and 2g of ferrous sulfate heptahydrate were added, and ammonia water was added dropwise to adjust the pH to alkaline (pH=8). The mixture was stirred for 2 hours to allow the reaction to proceed fully and the product was obtained. The product was washed multiple times by centrifugation with ethanol and deionized water, and then freeze-dried in a freeze dryer at -50 ℃ for about 24 hours to obtain the final product Fe3O4 / SiO2@PVDF.
[0031] 5) Modification of LLZO ceramic electrolytic sheets LLZO ceramic electrolytic sheets were pretreated by immersing them in a 20% (w / w) NaOH solution for 30 minutes, and then the NaOH solution on the surface of the LLZO ceramic electrolytic sheets was washed away with ethanol to obtain pretreated LLZO ceramic electrolytic sheets; ethanol, water, and N-(3-triethoxysilylpropyl)-4,5-dihydroimidazole were mixed in a volume ratio of V 乙醇 V 水 V DI A solution with a ratio of 9:2.5:1 was prepared and added to a two-necked flask to prepare a mixed solution. The pretreated LLZO ceramic electrolytic sheet was added to the mixed solution and ultrasonically dispersed for 30 min. Then, the mixture was refluxed in an oil bath at 75 °C with a spherical condenser for stirring and reacted for 24 h. The LLZO ceramic electrolytic sheet is prepared by the following method: garnet-type LLZO electrolyte conductor material is prepared by solid-state synthesis (refer to the existing patent application CN113363562 A), and LLZO ceramic sheet with a diameter of 10 mm and a thickness of 1 mm is prepared by pre-firing and debinding, and finally sintering in a muffle furnace.
[0032] 6) Preparation of LLZO / Fe3O4 / SiO2@PVDF composite solid electrolyte material 5 mL of N,N-dimethylamide, 1 g of matrix polyvinylidene fluoride, and 0.1 g of Fe3O4 / SiO2@PVDF prepared in step 4) were placed in a glass reagent bottle and stirred with a magnetic stirrer for 24 h to ensure uniform mixing. The mixture was then spread on the surface of an LLZO ceramic electrolytic sheet and baked in a vacuum oven at 80 °C for 24 h to obtain an LLZO / 0.1Fe3O4 / SiO2@PVDF composite solid electrolyte material. Example 2:
[0033] 1) Surface modification of SiO2 particles: 3g of commercially available SiO2 particles (15nm in diameter) were dispersed in 20mL of a mixed solution of ethanol and deionized water, with a volume ratio of ethanol to deionized water of 9:1. The solution was ultrasonically treated for about 45min to ensure uniform dispersion of the SiO2 particles, thus obtaining a SiO2 particle solution. The SiO2 particle solution was then mixed with 4mL of silane coupling agent 3-aminopropyltriethoxysilane (APTES) and reacted for 3 hours to modify the surface of the SiO2 particles. Finally, excess silane coupling agent was removed by centrifugation and the particles were washed.
[0034] 2) Preparation of PVDF latex seed solution Using water as the continuous phase, 0.24g of surfactant sodium dodecyl sulfate, 0.15g of initiator potassium persulfate, and 12g of polymerizable monomer vinyl fluoride were added to emulsify the monomer vinyl fluoride to form an oil / water emulsion. The polymerization was initiated by heating to form nano-sized PVDF latex particles, thus obtaining a PVDF latex seed solution.
[0035] 3) Preparation of SiO2@PVDF core-shell composite particles The surface-modified SiO2 particles from step 1) were ultrasonically dispersed in the PVDF latex seed solution prepared in step 2). SiO2 was anchored to the surface of the PVDF particles using electrostatic adsorption to obtain seed particles. Subsequently, 5g of the monomer vinyl fluoride was added, and the reaction temperature was controlled at 80℃ to continue polymerization. During polymerization, the vinyl fluoride molecules in the latex combine with the seed particles. The polymerization reaction time was 5 hours, allowing the monomer to grow on the surface of the seed particles, forming SiO2@PVDF core-shell composite particles. After the reaction, 0.1mL of carbon disulfide was added as a terminator to terminate the polymerization reaction. Unreacted vinyl fluoride and potassium persulfate initiator were removed by centrifugation. The obtained SiO2@PVDF core-shell composite particles were washed multiple times by centrifugation with deionized water and ethanol to remove residual reactants and the surfactant sodium dodecyl sulfate. Finally, the washed SiO2@PVDF core-shell composite particles were dried in a vacuum drying oven at 60℃ for 12 hours to room weight.
[0036] 4) Preparation of Fe3O4 / SiO2@PVDF 10g of SiO2@PVDF Janus core-shell composite particles were ultrasonically dispersed in 200 mL of distilled water in a three-necked flask, mechanically stirred, and argon gas was introduced. Then, 3g of anhydrous ferric chloride and 3g of ferrous sulfate heptahydrate were added, and ammonia water was added dropwise to adjust the pH to alkaline (pH=8). The mixture was stirred for 2 hours to fully react and obtain the product. The product was washed multiple times by centrifugation with ethanol and deionized water, and then freeze-dried in a freeze dryer at -50 ℃ for about 24 hours to obtain the final product Fe3O4 / SiO2@PVDF.
[0037] 5) Modification of LLZO ceramic electrolytic sheets LLZO ceramic electrolytic sheets (same as in Example 1) were pretreated by immersing them in a 20% (w / w) NaOH solution for 30 minutes, and then the NaOH solution on the surface of the LLZO ceramic electrolytic sheets was washed off with ethanol to obtain pretreated LLZO ceramic electrolytic sheets; ethanol, water and N-(3-triethoxysilylpropyl)-4,5-dihydroimidazole were mixed in a volume ratio of V 乙醇 V 水 V DI A solution with a ratio of 9:2.5:1 was prepared and added to a two-necked flask to prepare a mixed solution. The pretreated LLZO ceramic electrolytic sheet was added to the mixed solution and ultrasonically dispersed for 30 min. Then, the mixture was refluxed in an oil bath at 75 °C with a spherical condenser for stirring and a rotor, and reacted for 24 h.
[0038] 6) Preparation of LLZO / Fe3O4 / SiO2@PVDF composite solid electrolyte material 7 mL of N,N-dimethylamide, 1.5 g of matrix polyvinylidene fluoride, and 0.2 g of Fe3O4 / SiO2@PVDF prepared in step 4) were placed in a glass reagent bottle and stirred with a magnetic stirrer for 24 h to mix evenly. The mixture was then spread on the surface of an LLZO ceramic electrolytic sheet and baked in a vacuum oven at 80 °C for 24 h to obtain an LLZO / 0.2Fe3O4 / SiO2@PVDF composite solid electrolyte material. Example 3:
[0039] 1) Surface modification of SiO2 particles: 4g of commercially available SiO2 particles (15nm in diameter) were dispersed in 20mL of a mixed solution of ethanol and deionized water, with a volume ratio of ethanol to deionized water of 9:1. The solution was ultrasonically treated for about 60min to ensure uniform dispersion of the SiO2 particles, thus obtaining a SiO2 particle solution. The SiO2 particle solution was then mixed with 5mL of silane coupling agent 3-aminopropyltriethoxysilane (APTES) and reacted for 3 hours to modify the surface of the SiO2 particles. Finally, excess silane coupling agent was removed by centrifugation and the particles were washed.
[0040] 2) Preparation of PVDF latex seed solution Using water as the continuous phase, 0.18g of surfactant sodium dodecyl sulfate, 0.12g of initiator potassium persulfate, and 10g of polymeric monomer vinyl fluoride were added. The vinyl fluoride monomer was emulsified to form an oil / water emulsion, and polymerization was initiated by heating to form nano-sized PVDF latex particles, thus obtaining a PVDF latex seed solution.
[0041] 3) Preparation of SiO2@PVDF core-shell composite particles The surface-modified SiO2 particles from step 1) were ultrasonically dispersed in the PVDF latex seed solution prepared in step 2). SiO2 was anchored to the surface of the PVDF particles using electrostatic adsorption to obtain seed particles. Subsequently, 5g of the monomer vinyl fluoride was added, and the reaction temperature was controlled at 80℃ to continue polymerization. During polymerization, the vinyl fluoride molecules in the latex combine with the seed particles. The polymerization reaction time was 5 hours, allowing the monomer to grow on the surface of the seed particles, forming SiO2@PVDF core-shell composite particles. After the reaction, 0.15 mL of carbon disulfide was added as a terminator to terminate the polymerization reaction. Unreacted vinyl fluoride and potassium persulfate initiator were removed by centrifugation. The obtained SiO2@PVDF core-shell composite particles were washed multiple times by centrifugation with deionized water and ethanol to remove residual reactants and the surfactant sodium dodecyl sulfate. Finally, the washed SiO2@PVDF core-shell composite particles were dried in a vacuum drying oven at 60℃ for 12 hours to room weight.
[0042] 4) Preparation of Fe3O4 / SiO2@PVDF 10g of SiO2@PVDF core-shell composite particles were ultrasonically dispersed in 200 mL of distilled water in a three-necked flask, mechanically stirred, and argon gas was introduced. Then, 5g of anhydrous ferric chloride and 3g of ferrous sulfate heptahydrate were added, and ammonia water was added dropwise to adjust the pH to alkaline (pH=8). The mixture was stirred for 2 hours to fully react and obtain the product. The product was washed multiple times by centrifugation with ethanol and deionized water, and then freeze-dried in a freeze dryer at -50 ℃ for about 24 hours to obtain the final product Fe3O4 / SiO2@PVDF.
[0043] 5) Modification of LLZO ceramic electrolytic sheets LLZO ceramic electrolytic sheets (same as in Example 1) were pretreated by immersing them in a 20% (w / w) NaOH solution for 30 minutes, and then the NaOH solution on the surface of the LLZO ceramic electrolytic sheets was washed off with ethanol to obtain pretreated LLZO ceramic electrolytic sheets; ethanol, water and N-(3-triethoxysilylpropyl)-4,5-dihydroimidazole were mixed in a volume ratio of V 乙醇 V 水 V DI A solution with a ratio of 9:2.5:1 was prepared and added to a two-necked flask to prepare a mixed solution. The pretreated LLZO ceramic electrolytic sheet was added to the mixed solution and ultrasonically dispersed for 30 min. Then, the mixture was refluxed in an oil bath at 75 °C with a spherical condenser for stirring and a rotor, and reacted for 24 h.
[0044] 6) Preparation of LLZO / Fe3O4 / SiO2@PVDF composite solid electrolyte material 7 mL of N,N-dimethylamide, 1.5 g of matrix polyvinylidene fluoride, and 0.3 g of Fe3O4 / SiO2@PVDF prepared in step 4) were placed in a glass reagent bottle and stirred with a magnetic stirrer for 24 h to ensure uniform mixing. The mixture was then spread on the surface of an LLZO ceramic electrolytic sheet and baked in a vacuum oven at 80 °C for 24 h to obtain the LLZO / 0.3Fe3O4 / SiO2@PVDF composite solid electrolyte material. Figure 2 and Figure 3 The images show the microstructure and cross-sectional view of the LLZO / 0.3Fe3O4 / SiO2@PVDF sample synthesized in this embodiment. Example 4:
[0045] 1) Surface modification of SiO2 particles: 3g of commercially available SiO2 particles (15nm in diameter) were dispersed in 20mL of a mixed solution of ethanol and deionized water, with a volume ratio of ethanol to deionized water of 9:1. The solution was ultrasonically treated for about 30min to ensure uniform dispersion of the SiO2 particles, thus obtaining a SiO2 particle solution. The SiO2 particle solution was mixed with 4mL of silane coupling agent 3-aminopropyltriethoxysilane (APTES) and reacted for 3 hours to modify the surface of the SiO2 particles. Finally, excess silane coupling agent was removed by centrifugation and the particles were washed.
[0046] 2) Preparation of PVDF latex seed solution Using water as the continuous phase, 0.18 g of surfactant sodium dodecyl sulfate, 0.12 g of initiator potassium persulfate, and 10 g of polymeric monomer vinyl fluoride were added to emulsify the monomer vinyl fluoride to form an oil / water emulsion. The polymerization was initiated by heating to form nano-sized PVDF latex particles, thus obtaining a PVDF latex seed solution.
[0047] 3) Preparation of SiO2@PVDF core-shell composite particles The surface-modified SiO2 particles from step 1) were ultrasonically dispersed in the PVDF latex seed solution prepared in step 2). SiO2 was anchored to the surface of the PVDF particles using electrostatic adsorption to obtain seed particles. Subsequently, 5g of the monomer vinyl fluoride was added, and the reaction temperature was controlled at 80℃ to continue polymerization. During polymerization, the vinyl fluoride molecules in the latex combine with the seed particles. The polymerization reaction time was 5 hours, allowing the monomer to grow on the surface of the seed particles, forming SiO2@PVDF core-shell composite particles. After the reaction, 0.1mL of carbon disulfide was added as a terminator to terminate the polymerization reaction. Unreacted vinyl fluoride and potassium persulfate initiator were removed by centrifugation. The obtained SiO2@PVDF core-shell composite particles were washed multiple times by centrifugation with deionized water and ethanol to remove residual reactants and the surfactant sodium dodecyl sulfate. Finally, the washed SiO2@PVDF core-shell composite particles were dried in a vacuum drying oven at 60℃ for 12 hours to room weight.
[0048] 4) Preparation of Fe3O4 / SiO2@PVDF 10g of SiO2@PVDF core-shell composite particles were ultrasonically dispersed in 200 mL of distilled water in a three-necked flask, mechanically stirred, and argon gas was introduced. Then, 4g of anhydrous ferric chloride and 2g of ferrous sulfate heptahydrate were added, and ammonia water was added dropwise to adjust the pH to alkaline (pH=8). The mixture was stirred for 2 hours to allow the reaction to proceed fully and the product was obtained. The product was washed multiple times by centrifugation with ethanol and deionized water, and then freeze-dried in a freeze dryer at -50 ℃ for about 24 hours to obtain the final product Fe3O4 / SiO2@PVDF.
[0049] 5) Modification of LLZO ceramic electrolytic sheets LLZO ceramic electrolytic sheets (same as in Example 1) were pretreated by immersing them in a 20% (w / w) NaOH solution for 30 minutes, and then the NaOH solution on the surface of the LLZO ceramic electrolytic sheets was washed off with ethanol to obtain pretreated LLZO ceramic electrolytic sheets; ethanol, water and N-(3-triethoxysilylpropyl)-4,5-dihydroimidazole were mixed in a volume ratio of V 乙醇 V 水 V DI A solution with a ratio of 9:2.5:1 was prepared and added to a two-necked flask to prepare a mixed solution. The pretreated LLZO ceramic electrolytic sheet was added to the mixed solution and ultrasonically dispersed for 60 min. Then, the mixture was refluxed in an oil bath at 75 °C with a spherical condenser for stirring and reacted for 24 h.
[0050] 6) Preparation of LLZO / Fe3O4 / SiO2@PVDF composite solid electrolyte material 7 mL of N,N-dimethylamide, 1.4 g of matrix polyvinylidene fluoride, and 0.4 g of Fe3O4 / SiO2@PVDF prepared in step 4) were placed in a glass reagent bottle and stirred with a magnetic stirrer for 24 h to ensure uniform mixing. The mixture was then spread on the surface of an LLZO ceramic electrolytic sheet and baked in a vacuum oven at 80 °C for 24 h to obtain the LLZO / 0.4Fe3O4 / SiO2@PVDF composite solid electrolyte material. Example 5:
[0051] 1) Surface modification of SiO2 particles: 4g of commercially available SiO2 particles (15nm in diameter) were dispersed in 20mL of a mixed solution of ethanol and deionized water, with a volume ratio of ethanol to deionized water of 9:1. The solution was ultrasonically treated for about 30min to ensure uniform dispersion of the SiO2 particles, thus obtaining a SiO2 particle solution. The SiO2 particle solution was then mixed with 5mL of silane coupling agent 3-aminopropyltriethoxysilane (APTES) and reacted for 3 hours to modify the surface of the SiO2 particles. Finally, excess silane coupling agent was removed by centrifugation and the particles were washed.
[0052] 2) Preparation of PVDF latex seed solution Using water as the continuous phase, 0.3g of surfactant sodium dodecyl sulfate, 0.28g of initiator potassium persulfate, and 14g of polymeric monomer vinyl fluoride were added to emulsify the monomer vinyl fluoride to form an oil / water emulsion. The polymerization was initiated by heating to form nano-sized PVDF latex particles, thus obtaining a PVDF latex seed solution.
[0053] 3) Preparation of SiO2@PVDF core-shell composite particles The surface-modified SiO2 particles from step 1) were ultrasonically dispersed in the PVDF latex seed solution prepared in step 2). SiO2 was anchored to the surface of the PVDF particles using electrostatic adsorption to obtain seed particles. Subsequently, 5g of the monomer vinyl fluoride was added, and the reaction temperature was controlled at 80℃ to continue polymerization. During polymerization, the vinyl fluoride molecules in the latex combine with the seed particles. The polymerization reaction time was 5 hours, allowing the monomer to grow on the surface of the seed particles, forming SiO2@PVDF core-shell composite particles. After the reaction, 0.15mL of carbon disulfide was added as a terminator to terminate the polymerization reaction. Unreacted vinyl fluoride and potassium persulfate initiator were removed by centrifugation. The obtained SiO2@PVDF core-shell composite particles were washed multiple times by centrifugation with deionized water and ethanol to remove residual reactants and the surfactant sodium dodecyl sulfate. Finally, the washed SiO2@PVDF core-shell composite particles were dried in a vacuum drying oven at 60℃ for 12 hours to room weight.
[0054] 4) Preparation of Fe3O4 / SiO2@PVDF 10g of SiO2@PVDF core-shell composite particles were ultrasonically dispersed in 200mL of distilled water in a three-necked flask, mechanically stirred, and argon gas was introduced. Then, 5g of anhydrous ferric chloride and 2g of ferrous sulfate heptahydrate were added, and ammonia water was added dropwise to adjust the pH to alkaline (pH=8). The mixture was stirred for 2 hours to allow the reaction to proceed fully and the product was obtained. The product was washed multiple times by centrifugation with ethanol and deionized water, and then freeze-dried in a freeze dryer at -50 ℃ for about 24 hours to obtain the final product Fe3O4 / SiO2@PVDF.
[0055] 5) Modification of LLZO ceramic electrolytic sheets LLZO ceramic electrolytic sheets (same as in Example 1) were pretreated by immersing them in a 20% (w / w) NaOH solution for 30 minutes, and then the NaOH solution on the surface of the LLZO ceramic electrolytic sheets was washed off with ethanol to obtain pretreated LLZO ceramic electrolytic sheets; ethanol, water and N-(3-triethoxysilylpropyl)-4,5-dihydroimidazole were mixed in a volume ratio of V 乙醇 V 水 V DI A solution with a ratio of 9:2.5:1 was prepared and added to a two-necked flask to prepare a mixed solution. The pretreated LLZO ceramic electrolytic sheet was added to the mixed solution and ultrasonically dispersed for 40 min. Then, the mixture was refluxed in an oil bath at 75 °C with a spherical condenser for stirring and reacted for 24 h.
[0056] 6) Preparation of LLZO / Fe3O4 / SiO2@PVDF composite solid electrolyte material 8 mL of N,N-dimethylamide, 1.6 g of matrix polyvinylidene fluoride, and 0.5 g of Fe3O4 / SiO2@PVDF prepared in step 4) were placed in a glass reagent bottle and stirred with a magnetic stirrer for 24 h to ensure uniform mixing. The mixture was then spread on the surface of an LLZO ceramic electrolytic sheet and baked in a vacuum oven at 80 °C for 24 h to obtain the LLZO / 0.5Fe3O4 / SiO2@PVDF composite solid electrolyte material. Example 6:
[0057] 1) Surface modification of SiO2 particles: 2g of commercially available SiO2 particles (15nm in diameter) were dispersed in 20mL of a mixed solution of ethanol and deionized water, with a volume ratio of ethanol to deionized water of 9:1. The solution was ultrasonically treated for about 50min to ensure uniform dispersion of the SiO2 particles, thus obtaining a SiO2 particle solution. The SiO2 particle solution was then mixed with 3mL of silane coupling agent 3-aminopropyltriethoxysilane (APTES) and reacted for 2.5h to modify the surface of the SiO2 particles. Finally, excess silane coupling agent was removed by centrifugation and the particles were washed.
[0058] 2) Preparation of PVDF latex seed solution Using water as the continuous phase, 0.24 g of surfactant sodium dodecyl sulfate, 0.15 g of initiator potassium persulfate, and 12 g of polymeric monomer vinyl fluoride were added to emulsify the monomer vinyl fluoride to form an oil / water emulsion. The polymerization was initiated by heating to form nano-sized PVDF latex particles, thus obtaining a PVDF latex seed solution.
[0059] 3) Preparation of SiO2@PVDF core-shell composite particles The surface-modified SiO2 particles from step 1) were ultrasonically dispersed in the PVDF latex seed solution prepared in step 2). SiO2 was anchored to the surface of the PVDF particles using electrostatic adsorption to obtain seed particles. Subsequently, 5g of the monomer vinyl fluoride was added, and the reaction temperature was controlled at 80℃ to continue polymerization. During polymerization, the vinyl fluoride molecules in the latex combine with the seed particles. The polymerization reaction time was 5 hours, allowing the monomer to grow on the surface of the seed particles, forming SiO2@PVDF core-shell composite particles. After the reaction, 0.05mL of carbon disulfide was added as a terminator to terminate the polymerization reaction. Unreacted vinyl fluoride, solvent, and potassium persulfate initiator were removed by centrifugation. The obtained SiO2@PVDF core-shell composite particles were washed multiple times by centrifugation with deionized water and ethanol to remove residual reactants and the surfactant sodium dodecyl sulfate. Finally, the washed SiO2@PVDF core-shell composite particles were dried in a vacuum drying oven at 60℃ for 12 hours to room weight.
[0060] 4) Preparation of Fe3O4 / SiO2@PVDF 10g of SiO2@PVDF core-shell composite particles were ultrasonically dispersed in 200 mL of distilled water in a three-necked flask, mechanically stirred, and argon gas was introduced. Then, 4g of anhydrous ferric chloride and 3g of ferrous sulfate heptahydrate were added, and ammonia water was added dropwise to adjust the pH to alkaline (pH=8). The mixture was stirred for 2 hours to allow the reaction to proceed fully and the product was obtained. The product was washed multiple times by centrifugation with ethanol and deionized water, and then freeze-dried in a freeze dryer at -50 ℃ for about 24 hours to obtain the final product Fe3O4 / SiO2@PVDF.
[0061] 5) Modification of LLZO ceramic electrolytic sheets LLZO ceramic electrolytic sheets (same as in Example 1) were pretreated by immersing them in a 20% (w / w) NaOH solution for 30 minutes, and then the NaOH solution on the surface of the LLZO ceramic electrolytic sheets was washed off with ethanol to obtain pretreated LLZO ceramic electrolytic sheets; ethanol, water and N-(3-triethoxysilylpropyl)-4,5-dihydroimidazole were mixed in a volume ratio of V 乙醇 V 水 V DIA solution with a ratio of 9:2.5:1 was prepared and added to a two-necked flask to prepare a mixed solution. The pretreated LLZO ceramic electrolytic sheet was added to the mixed solution and ultrasonically dispersed for 45 min. Then, the mixture was refluxed in an oil bath at 75 °C with a spherical condenser for stirring and a rotor, and reacted for 24 h.
[0062] 6) Preparation of LLZO / Fe3O4 / SiO2@PVDF composite solid electrolyte material 7 mL of N,N-dimethylamide, 1.4 g of matrix polyvinylidene fluoride, and 0.25 g of Fe3O4 / SiO2@PVDF prepared in step 4) were placed in a glass reagent bottle and stirred with a magnetic stirrer for 24 h to ensure uniform mixing. The mixture was then spread on the surface of an LLZO ceramic electrolytic sheet and baked in a vacuum oven at 80 °C for 24 h to obtain the LLZO / 0.25Fe3O4 / SiO2@PVDF composite solid electrolyte material. Example 7:
[0063] 1) Surface modification of SiO2 particles: 2g of commercially available SiO2 particles (15nm in diameter) were dispersed in 20mL of a mixed solution of ethanol and deionized water, with a volume ratio of ethanol to deionized water of 9:1. The solution was ultrasonically treated for about 50min to ensure uniform dispersion of the SiO2 particles, thus obtaining a SiO2 particle solution. The SiO2 particle solution was then mixed with 3mL of silane coupling agent 3-aminopropyltriethoxysilane (APTES) and reacted for 2.5h to modify the surface of the SiO2 particles. Finally, excess silane coupling agent was removed by centrifugation and the particles were washed.
[0064] 2) Preparation of PVDF latex seed solution Using water as the continuous phase, 0.18 g of surfactant sodium dodecyl sulfate, 0.12 g of initiator potassium persulfate, and 10 g of polymeric monomer vinyl fluoride were added to emulsify the monomer vinyl fluoride to form an oil / water emulsion. The polymerization was initiated by heating to form nano-sized PVDF latex particles, thus obtaining a PVDF latex seed solution.
[0065] 3) Preparation of SiO2@PVDF core-shell composite particles The surface-modified SiO2 particles from step 1) were ultrasonically dispersed in the PVDF latex seed solution prepared in step 2). SiO2 was anchored to the surface of the PVDF particles using electrostatic adsorption to obtain seed particles. Subsequently, 5g of the monomer vinyl fluoride was added, and the reaction temperature was controlled at 60℃ to continue polymerization. During polymerization, the vinyl fluoride molecules in the latex combine with the seed particles. The polymerization reaction time was 5 hours, allowing the monomer to grow on the surface of the seed particles, forming SiO2@PVDF core-shell composite particles. After the reaction, 0.05mL of carbon disulfide was added as a terminator to terminate the polymerization reaction. Unreacted vinyl fluoride and potassium persulfate initiator were removed by centrifugation. The obtained SiO2@PVDF core-shell composite particles were washed multiple times by centrifugation with deionized water and ethanol to remove residual reactants and the surfactant sodium dodecyl sulfate. Finally, the washed SiO2@PVDF core-shell composite particles were dried in a vacuum drying oven at 60℃ for 12 hours to room weight.
[0066] 4) Preparation of Fe3O4 / SiO2@PVDF 10g of SiO2@PVDF core-shell composite particles were ultrasonically dispersed in 200mL of distilled water in a three-necked flask, mechanically stirred, and argon gas was introduced. Then, 3g of anhydrous ferric chloride and 2g of ferrous sulfate heptahydrate were added, and ammonia water was added dropwise to adjust the pH to alkaline (pH=8). The mixture was stirred for 2 hours to allow the reaction to proceed fully and the product was obtained. The product was washed multiple times by centrifugation with ethanol and deionized water, and then freeze-dried in a freeze dryer at -50 ℃ for about 24 hours to obtain the final product Fe3O4 / SiO2@PVDF.
[0067] 5) Modification of LLZO ceramic electrolytic sheets LLZO ceramic electrolytic sheets (same as in Example 1) were pretreated by immersing them in a 20% (w / w) NaOH solution for 30 minutes, and then the NaOH solution on the surface of the LLZO ceramic electrolytic sheets was washed off with ethanol to obtain pretreated LLZO ceramic electrolytic sheets; ethanol, water and N-(3-triethoxysilylpropyl)-4,5-dihydroimidazole were mixed in a volume ratio of V 乙醇 V 水 V DI A solution with a ratio of 9:2.5:1 was prepared and added to a two-necked flask to prepare a mixed solution. The pretreated LLZO ceramic electrolytic sheet was added to the mixed solution and ultrasonically dispersed for 60 min. Then, the mixture was refluxed in an oil bath at 75 °C with a spherical condenser for stirring and reacted for 24 h.
[0068] 6) Preparation of LLZO / Fe3O4 / SiO2@PVDF composite solid electrolyte material 5 mL of N,N-dimethylamide, 1 g of matrix polyvinylidene fluoride, and 0.35 g of Fe3O4 / SiO2@PVDF prepared in step 4) were placed in a glass reagent bottle and stirred with a magnetic stirrer for 24 h to ensure uniform mixing. The mixture was then spread on the surface of an LLZO ceramic electrolytic sheet and baked in a vacuum oven at 80 °C for 24 h to obtain the LLZO / 0.35Fe3O4 / SiO2@PVDF composite solid electrolyte material.
[0069] Comparative Example 1:
[0070] In step (5), during the modification of the LLZO ceramic electrolytic sheet, DI modification is not performed, and the rest is the same as in Example 3.
[0071] Comparative Example 2:
[0072] Step (4) Preparation of Fe3O4 / SiO2@PVDF is omitted; the rest is the same as in Example 3.
[0073] Comparative Example 3:
[0074] The preparation of Fe3O4 / SiO2@PVDF in step (4) is omitted, and DI modification is not performed in the modification process of LLZO ceramic electrolytic sheet in step (5). The rest is the same as in Example 3.
[0075] Comparative Example 4:
[0076] In step (2), the preparation of latex seed solution, PEO was selected instead of PVDF, and the rest was the same as in Example 3.
[0077] The preparation process of the latex seed solution is as follows: 10 mg of PEO-based copolymer (PEO-PLA) is dissolved in 2 mL of organic solvent THF. 20 mL of deionized water is measured and poured into a 50 mL beaker. The mixture is pre-stirred (500 rpm). Using a syringe, 2 mL of the copolymer / THF solution is slowly added dropwise to the aqueous phase at a rate of 1 mL / min. Stirring is maintained (1000 rpm) for 2 hours to allow the THF to evaporate. The solution is transferred to a dialysis bag (MWCO 3.5 kDa) and dialyzed against deionized water for 24 hours (changing the water 3-4 times) to remove residual solvent and free molecules. Finally, the solution is centrifuged to obtain the PEO latex seed solution.
[0078] The room temperature conductivity of each component sample of the LLZO / xFe3O4 / SiO2@PVDF (0<x≤0.5) composite solid electrolyte material was determined using Archimedes' water displacement method and the formula for calculating ionic conductivity σ=L / RS, where L represents the sample thickness and S represents the electrode area. The results are shown in Tables 1 and 2.
[0079] Table 1 shows the shrinkage, density, and electrical conductivity of the LLZO / xFe3O4 / SiO2@PVDF (0<x≤0.5) system at 30℃.
[0080] Table 2 shows the shrinkage, density, and conductivity of the LLZO / xFe3O4 / SiO2@PVDF (x=0, 0.3) system at 30℃.
[0081] As shown in Table 1, with the increase of Fe3O4 / SiO2@PVDF modified LLZO ceramic electrolyte content, the density, shrinkage rate, and conductivity of the LLZO / xFe3O4 / SiO2@PVDF (0<x≤0.5) composite solid electrolyte material gradually increased. Among them, the density, shrinkage rate, and ionic conductivity of LLZO / 0.3Fe3O4 / SiO2@PVDF reached the highest, at 96%, 9.7%, and 5.09×10⁻⁶, respectively. -4 S / cm, while excessive Fe3O4 particles will accumulate on or inside the LLZO surface, forming a discontinuous particle layer. This will hinder the transport path of lithium ions in LLZO, increase the resistance to ion migration, and thus reduce ionic conductivity. Figure 1 This paper describes how the imidazole groups of LLZO-DI achieved coordination with Janus materials, thereby realizing the interfacial bonding between the electrode and the composite electrolyte. The improved LLZO / Janus / PVDF interface ensures rapid Li-ionization. + The formation of conductive tunnels provides a new approach for the design of novel all-solid composite electrolytes.
[0082] As shown in Table 2, Comparative Example 1, without DI modification of the composite electrolyte, failed to exhibit good physical and electrochemical properties. This is because it lacks the imidazole group in LLZO-DI, which coordinates with the Janus material, enabling interfacial bonding between the electrode and the composite electrolyte, thus achieving the purpose of interface modification. Comparative Examples 2 and 3 lacked Fe3O4 nanoparticles, resulting in poor electrochemical performance. Fe3O4 nanoparticles can improve the ionic conductivity of the interface and reduce interfacial impedance by improving interfacial compatibility. Comparative Example 4 used PEO instead of PVDF, but did not exhibit good performance because PEO's rigidity and flexibility are inferior to PVDF, and its ionic conductivity is temperature-dependent. PEO is easily oxidized and decomposed under high voltage (>4V) conditions, limiting its application in high-energy-density batteries. Figure 4The AC impedance spectra of the ceramic samples synthesized in Examples 1, 3, and 5 of this invention, as well as the synthesized LLZO / xFe3O4 / SiO2@PVDF (x=0.1, 0.3, 0.5) and the LLZO / SiO2@PVDF ceramic samples synthesized in Comparative Example 2, are shown. Figure 5 The samples synthesized and assembled into coin cells LFP / LLZO / xFe3O4 / SiO2@PVDF / Li (x=0.1, 0.3, 0.5) in Examples 1, 3, 5 and Comparative Example 2 of this invention are shown, and their cycle performance at 0.1C is evaluated.
Claims
1. A method for preparing a composite solid electrolyte based on a root-soil interlocking structure constructed from Janus particles, characterized in that: The preparation steps are as follows: 1) Surface modification of SiO2 particles SiO2 particles were dispersed in a mixed solution of ethanol and deionized water and treated with ultrasound to ensure uniform dispersion of the SiO2 particles, thus obtaining a SiO2 particle solution. The SiO2 particle solution was then mixed with the coupling agent 3-aminopropyltriethoxysilane, and centrifuged and washed after the reaction was complete. 2) Preparation of PVDF latex seed solution Using water as the continuous phase, sodium dodecyl sulfate surfactant, potassium persulfate initiator and vinyl fluoride monomer are added to emulsify the vinyl fluoride monomer to form an oil / water emulsion. Polymerization is initiated by heating to form nano-sized PVDF latex particles, thus preparing a PVDF latex seed solution. 3) Preparation of SiO2@PVDF core-shell composite particles The surface-modified SiO2 particles from step 1) were ultrasonically dispersed in the PVDF latex seed solution prepared in step 2). The SiO2 particles were anchored to the surface of the PVDF latex particles by electrostatic adsorption to obtain seed particles. Subsequently, the polymeric monomer vinyl fluoride was added and the reaction temperature was controlled to continue initiating polymerization, allowing the polymeric monomer vinyl fluoride to grow on the surface of the seed particles to form SiO2@PVDF core-shell composite particles. After the reaction was completed, carbon disulfide was added as a terminator to terminate the polymerization reaction. The obtained SiO2@PVDF core-shell composite particles were then washed by centrifugation with deionized water and ethanol. Finally, the SiO2@PVDF core-shell composite particles were obtained after vacuum drying. 4) Preparation of Fe3O4 / SiO2@PVDF The SiO2@PVDF core-shell composite particles obtained in step 3) were ultrasonically dispersed in distilled water, mechanically stirred and argon gas was introduced, then anhydrous ferric chloride and ferrous sulfate heptahydrate were added, and ammonia water was added dropwise to adjust the pH to alkaline. The mixture was stirred to react fully. The product was washed with ethanol and deionized water by centrifugation, and then freeze-dried in a freeze dryer under vacuum to obtain the product Fe3O4 / SiO2@PVDF. 5) Modification of LLZO ceramic electrolytic sheets LLZO ceramic electrolytic sheets were pretreated by immersing them in NaOH solution, and then the NaOH solution on the surface of the LLZO ceramic electrolytic sheets was washed away with ethanol to obtain pretreated LLZO ceramic electrolytic sheets. Ethanol, water and N-(3-triethoxysilylpropyl)-4,5-dihydroimidazole were mixed in a certain proportion to prepare a mixed solution. The pretreated LLZO ceramic electrolytic sheets were added to the mixed solution and ultrasonically dispersed, and then subjected to reflux reaction. 6) Preparation of LLZO / Fe3O4 / SiO2@PVDF composite solid electrolyte material N,N-dimethylamide, polyvinylidene fluoride matrix, and Fe3O4 / SiO2@PVDF prepared in step 4) were mixed and stirred evenly, then spread on the surface of LLZO ceramic electrolytic sheet, and baked in a vacuum oven to obtain LLZO / Fe3O4 / SiO2@PVDF composite solid electrolyte material, that is, composite solid electrolyte based on Janus particles constructing root-soil interlocking structure.
2. The preparation method according to claim 1, characterized in that: The SiO2 particles in step 1) have a particle size of 15 nm, and the mass-to-volume ratio of the SiO2 particles to the mixed solution is (1-2) g: 10 mL. The mixed solution is prepared by mixing ethanol and deionized water at a volume ratio of 9:1, and the ultrasonic treatment time is 30-60 min. The mass-to-volume ratio of the SiO2 particle solution to the coupling agent 3-aminopropyltriethoxysilane is 20: (3-5).
3. The preparation method according to claim 1, characterized in that: In step 2), the mass ratio of the surfactant sodium dodecyl sulfate to the polymeric monomer vinyl fluoride is (0.18-0.3):(10-14); and the mass ratio of the initiator potassium persulfate to the polymeric monomer vinyl fluoride is (0.12-0.28):(10-14).
4. The preparation method according to claim 1, characterized in that: In step 3), the mass-to-volume ratio of the polymerizable monomer vinyl fluoride to the terminator carbon disulfide is 1 g: (0.01-0.03) mL, and the reaction temperature for initiating polymerization is controlled at 60℃-80℃.
5. The preparation method according to claim 1, characterized in that: In step 4), the mass-to-volume ratio of the SiO2@PVDF core-shell composite particles to distilled water is 1g:20mL, and the mass ratio of the SiO2@PVDF core-shell composite particles to anhydrous ferric chloride and ferrous sulfate heptahydrate is 10:(3-5):(2-3).
6. The preparation method according to claim 1, characterized in that: The volume ratio of ethanol, water and N-(3-triethoxysilylpropyl)-4,5-dihydroimidazole in step 5) is 9:2.5:
1.
7. The preparation method according to claim 6, characterized in that: In step 5), the pretreated LLZO ceramic electrolytic sheet is added to the mixed solution and ultrasonically dispersed for 30-60 min. Then, it is refluxed in an oil bath at 75°C with a spherical condenser tube for stirring, and the reaction is carried out for 24 h.
8. The preparation method according to claim 1, characterized in that: The volume-to-mass ratio of N,N-dimethylamide, polyvinylidene fluoride and Fe3O4 / SiO2@PVDF in step 6) is (5-8) mL: (1-1.6) g: (0.1-0.5) g.
9. The preparation method according to claim 8, characterized in that: In step 6), the temperature of the vacuum oven is 80℃ and the baking time is 24 hours.
Citation Information
Patent Citations
Preparation method of low-resistivity garnet type modified LLZO solid electrolyte
CN113363562A
Metal organic framework-polymer composite solid electrolyte as well as preparation method and application thereof
CN113937363A
Electrostatic spinning fiber membrane with organic-inorganic coupled Jauns structure, preparation method and application thereof
CN117684323A